Deformasi di Sumatera Barat Berdasarkan Data Pengamatan GPS Tahun 2002-2009 dan Dampak Kerusakan Lingkungan Akibat Gempa 30 September Tahun 2009 - Riko Maiyudi; Ikhwan Permana; Muhammad Ridholfi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. West Sumatra is a province located in an earthquake area. West Sumatra is located between the Eurasian Plate and Indo Australian plates. From 2002 until 2009, there were many earthquakes in the Sumatra region. In 2009 there was a major earthquake it caused many people dead, environmental damage and material losses in the West Sumatra. This is the reason for deformation studies in West Sumatra. The focus of the deformation study needed in West Sumatra is to mitigate future disasters. This deformation measurement is done by Geodetic GPS . The Geodetic GPS measurement data results are obtained from the Sumatra Array GPS data (SuGAr). The Geodetic GPS Measurement Data is then processed using software Gamit 10.5. From the results of data processing, there was accumulation of strains in 2002-2008 along the coast of central Sumatra which has the potential for earthquakes. And in 2009 on September 30 there was an earthquake that could be seen by a significant change in position during the pastoral era in the West Sumatra region. By studying as early as possible deformation in West Sumatra, it is expected that in the future the risk of environmental damage and losses due to earthquake disasters can be minimized.Keywords: Deformation, Environmental Damage, Earthquakes